As contribuições do teatro científico para a divulgação científica mediante a abordagem do tema lua - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
This research aims to analyze the implications of the Scientific Theater for Scientific Dissemination, through the preparation of the actor, construction of the show and presentation of a theater play with an approach on the Moon. The research was carried out from the perspective of qualitative analysis. For data collection, a theatrical workshop with seven meetings with the theme Lua was held, the participants were part of the school community of the State University of Ponta Grossa, the workshop culminated in a presentation of the play. The data were obtained through the audio-recorded logbook, recordings, focus group, questionnaires, footage and text of the play. For data analysis, the methodology of content analysis by Bardin (2003) was used. The results found point to the need for the actor's preparation through theatrical techniques so that they become a tool to disseminate scientific knowledge, among the elucidated techniques are: voice, breathing, grounding and referential look. The data also point out the necessary actions for the creation of scientific theatrical scenes as an actor preparation process, namely: choosing a reference, relating the reference to scientific knowledge, relating Science and Art, acting and disseminating scientific knowledge. The results also reveal that when creating a discourse to be disseminated through a theatrical script it is necessary to understand the viewer, create a connection with the viewer and reformulate the message to be disseminated and, finally, the reception of the discourse by the spectators takes place through communicational elements, which are: speech, scenography, actions, costumes and lighting.
Keywords: Ensino de Ciências; Teatro Científico; Divulgação Científica; Science Teaching; Scientific Theater; Scientific Dissemination; CNPQ::CIENCIAS EXATAS E DA TERRA